2006
DOI: 10.1111/j.1365-2141.2006.06275.x
|View full text |Cite|
|
Sign up to set email alerts
|

Pleiotropic role of histone deacetylases in the regulation of human adult erythropoiesis

Abstract: Summary Histone acetylation and deacetylation play fundamental roles in transcriptional regulation. We investigated the role of histone deacetylases (HDACs) in human adult haematopoiesis, using the structurally distinct HDAC inhibitors FK228 (depsipeptide) and Trichostatin A. When CD34+ cells were cultured with interleukin (IL)‐3 or stem cell factor (SCF) + IL‐3, FK228 (0·5 ng/ml) specifically enhanced the generation of immature erythroid cells with a CD36+ glycophorin A (GPA)low phenotype. In semisolid cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…In red cells, HDAC negatively regulate the interleukin-3-mediated growth of early erythroid precursors by suppressing their responsiveness to interleukin-3, and play an important role in erythropoietin-mediated differentiation and survival of erythroid precursors. 20 HDAC also play critical roles in terminal erythropoiesis. Popova et al recently demonstrated that the activities of HDAC are required for chromatin condensation in Friendvirus infected murine spleen erythroblasts (FVA cells).…”
Section: Introductionmentioning
confidence: 99%
“…In red cells, HDAC negatively regulate the interleukin-3-mediated growth of early erythroid precursors by suppressing their responsiveness to interleukin-3, and play an important role in erythropoietin-mediated differentiation and survival of erythroid precursors. 20 HDAC also play critical roles in terminal erythropoiesis. Popova et al recently demonstrated that the activities of HDAC are required for chromatin condensation in Friendvirus infected murine spleen erythroblasts (FVA cells).…”
Section: Introductionmentioning
confidence: 99%
“…Valproic acid (VPA), a non-selective HDACI, was reported to sustains the expression of stemness-related markers in hematopoietic stem/progenitor cells and enhance erythrocyte and megakaryocyte differentiation, by up-regulating genes of growth factor-independent protein 1B (GFI1B) and mixed-lineage leukemia translocated to chromosome 3 protein (MLLT3), mediated by the histone hyperacetylation at their promoter sites 49 . HDACIs FK228 and VPA also enhances the potential of interleukin-3 to stimulate erythropoiesis and megakaryopoiesis 50,51 . Our results showed that Tubastatin A does not affect platelet number significantly, which indicates that selective inhibition of HDAC6 might have different effect on hematopoietic stem/progenitor cells, compared to nonselective HDACIs.…”
Section: Discussionmentioning
confidence: 99%
“…10 Treatment of primary human progenitors with HDAC inhibitors strongly promotes erythroid lineage commitment and allows for erythroid differentiation in the absence of erythropoietin. 25,26 In addition, signaling elements upstream of PKD, PLC-␥1, and PKC-⑀ are activated by erythropoietin and have been implicated in erythropoietic regulation. 31,32 PLC-␥1 null mice display embryonic lethality at day 9.5-10.5 of development with complete absence of erythroid progenitors but no deficit of granulocyte or monocyte progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that erythropoietin signaling may cooperate with GATA1 activation through HDAC inhibition, extending previous observations in which HDAC inhibitors promoted erythropoietin-independent erythroid maturation of human progenitors. 25,26 PKD directly phosphorylates class IIa HDACs on conserved serine residues; the phosphorylated HDACs then undergo dissociation from transcriptional complexes, promoting derepression of target genes. 8,9 Class IIa HDACs expressed in G1ER cells and human erythroid progenitors included HDAC4 and HDAC5, the former cytosolic and the latter nuclear ( Figure 3F-G).…”
Section: Involvement Of Hdac5 In Erythropoietin Cooperation With Gata1mentioning
confidence: 99%